Dietary synbiotic ameliorates constipation through the modulation of gut microbiota and its metabolic function. (September 2021) - Yang, Zhandong; Ye, Simin; Xu, Zengmei; Su, Huihui; Tian, Xing; Han, Bo; Shen, Baochun; Liao, Qiongfeng; Xie, Zhiyong; Hong, Yanjun
Graphical abstract: Highlights: Synbiotic effectively ameliorates constipation symptoms in rats. Synbiotic increases relative abundances of Lactobacillus and Faecalibaculum in constipated rats. Synbiotic improves serum excitatory neurotransmitter levels in constipated rats. Synbiotic promotes fecal propionate and butyrate production in constipation rats. Synbiotic inhibits inflammatory responses in constipated rats. Abstract: The purpose of this study is to investigate the mitigatory effect of a novel synbiotic (SBT) on constipation from the perspective of gut microbiome and metabolome. Here, intake of SBT effectively attenuated diphenoxylate-induced constipation, recuperated colonic epithelial integrity and increased serum levels of gastrointestinal excitatory neurotransmitters (P substance, vasoactive intestinal peptide, motilin, gastrin and serotonin). 16S rRNA sequencing showed that SBT intake rehabilitated the composition and functionality of gut microbiota. Relative abundances of short-chain fatty acids (SCFAs)-producing bacteria including Lactobacillus, Faecalibaculum and Bifidobacterium were elevated by administration of SBT. The gas chromatography-mass spectrometry analysis confirmed that fecal concentrations of propionate and butyrate were significantly increased in the rats intervened with SBT. In addition, SBT ingestion reduced the relative levels of opportunistic pathogens, such as Oscillibacter, Parasutterella and Parabacteroides . Microbial functional prediction showed that the relative abundances of lipopolysaccharide (LPS) biosynthesis and arachidonic acid metabolism were downregulated with SBT administration, which were in accordance with the serum metabolomics results. Furthermore, serum levels of LPS, tumour necrosis factor alpha and interleukin 6 were significantly decreased, indicating that SBT supplementation suppressed inflammatory responses. Therefore, this study demonstrated that consumption of SBT ameliorated constipation possibly by regulating gut microbiota, promoting the SCFAs production and inhibiting inflammatory responses in rats. Our study also indicated that SBT may provide a novel alternative strategy for the treatment of constipation clinically in future.